Bolton tooth size ratio and its relation with arch widths, arch length and arch perimeter: A cone beam computed tomography (CBCT) study. (November 2014) - Alam, Mohammad Khursheed; Shahid, Fazal; Purmal, Kathiravan; Ahmad, Basaruddin; Khamis, Mohd Fadhli
Abstract Objective. The prime aim of the study was to measure and compare the 3D CBCT Bolton tooth size ratio in relation to the upper and lower arch widths, arch length and arch perimeter. Materials and methods. The data source was CBCT high volumetric data from the archives. Tooth size, arch widths, arch length and arch perimeter were measured in maxilla and mandibular arches. The independent t-test and ANOVA were used for statistical analyses. Results. The female Bolton anterior ratio (BAR) (78.373) and Bolton overall ratio (BOR) (93.231) show a greater tooth size ratio in comparison to male BAR (77.162) and BOR (93.124), respectively. However, no significant difference was found in the sexual comparison of all the measurements. Tooth size ratio in arch width groups also showed no significant difference. Significant discrepancies in the arch length (p < 0.05) groups and overall ratio and in the arch perimeter groups (p < 0.05 and p < 0.01) and anterior ratio were revealed. Conclusions. Tooth size ratios during orthodontic treatment for different arch length and arch perimeter groups need to be evaluated carefully.